Role of Rck-Pat1b binding in assembly of processing-bodies - Özgür, Sevim; Stoecklin, Georg (RNA biology, 2013)
The DEAD box RNA helicase Rck and the scaffold protein Pat1b participate in controlling gene expression at the post-transcriptional level by suppressing mRNA translation and promoting mRNA decapping. In addition, both proteins are required for the assembly of processing (P)-bodies, cytoplasmic foci that contain stalled mRNAs and numerous components of the mRNA decay machinery. The C-terminal RecA-like domain of Rck interacts with the N-terminal acidic domain of Pat1b. Here, we identified point mutations in human Rck and Pat1b that prevent the two proteins from binding to each other. By analyzing interaction-deficient mutants in combination with knockdown and rescue strategies in human HeLa cells, we found that Pat1b assembles P-bodies and suppresses expression of tethered mRNAs in the absence of Rck binding. In contrast, Rck requires the Pat1b-binding site in order to promote P-body assembly and associate with the decapping enzyme Dcp2 as well as Ago2 and TNRC6A, two core components of the RNA-induced silencing complex. Our data indicate that P-body assembly occurs in a step-wise manner, where Rck participates in the initial suppression of mRNA translation, whereas Pat1b in a second step triggers P-body assembly and promotes mRNA decapping.
Gesehen am 13.12.2021